Relationship development in insurance selling : a script-theoretic approach. - Tan, Jan Ai Kiang. (2009)
The purpose of this study is to obtain the grand selling scripts of effective and less effective salespersons. The study also attempts to investigate the cognitive knowledge of salespersons using the script-theoretic approach. That is, this research explores how effective and ineffective salesperson's knowledge bases may differ in terms of elaborateness, contingency, hypotheticality, and uniqueness. Comparisons among the groups are also made so as to identify differences that may exist based on the typicality of the selling situations. The extent to which effective and ineffective salespersons differ in the emphasis placed on relationship building is studied across selling situations as well. Further, the influence of self-monitoring is studied to provide understanding of its impact on selling knowledge and relationship building emphasis.